Comparison of radiotherapy infrastructure between Korea and Japan. (28th October 2019) - Huh, Seung Jae; Nishimura, Tetsuo; Park, Won; Nakamura, Katsumasa
Abstract: Background: Patterns of cancer incidence and radiotherapy use are similar in Korea and Japan, with differences in radiotherapy infrastructure. Methods: The authors surveyed the megavoltage machines in 91 radiotherapy centers in Korea and published data in Japan. The number of megavoltage machines per center was used as an indicator of the fragmentation of radiotherapy services using four as the threshold, and the number of megavoltage machines per million people was compared. The practice pattern of intensity-modulated radiation therapy was analyzed. Results: There were 91 centers in Korea and 825 in Japan. The number of megavoltage machines per center was 1.3 in Japan and 2.3 in Korea. Radiotherapy infrastructure showed fragmentation in Korea and hyperfragmentation in Japan. In Japan, 75% of radiotherapy centers operated with one megavoltage machine, whereas in Korea, 47% megavoltage machines per center was 3.2 in Seoul, while that in the non-capital area was 1.8, constituting a mixed pattern of centralization and fragmentation. In Japan, megavoltage machines per center in Tokyo, Kanagawa and Osaka, was 1.5, 1.3 and 1.2, respectively, indicating no concentration in the metropolis. The number of megavoltage machines per million in Korea was 4.0, whereas that in Seoul was 8.7, constituting capital concentration. In Japan, the number of megavoltage machines per million was 8.7, whereas in Tokyo, Kanagawa and Osaka, it was is 9.3, 6.3 and 9.0, showing uniform distribution. intensity-modulated radiation therapy utilization is increasing, accounting for 15% and 23% of radiotherapy patients in Japan and Korea, respectively. Conclusions: The fragmentation of radiotherapy services in Korea and Japan might affect radiotherapy quality. Abstract : Radiotherapy infrastructure showed fragmentation with a capital concentration in Korea and hyperfragmentation in Japan. Fragmentation in radiotherapy services might affect quality because quality assurance is necessary for high-technology radiotherapy.